Processus, modèles, produits - comment des étudiants polonais traduisent Flaubert - Dąmbska-Prokop, Urszula (Studia Romanica Posnaniensia, 2003)
The author presents an analysis of translations of fragments of G. Flaubert’s Madame Bovary by 19 students, concentrating on types of errors and difficulties encountered during this exercise. In the next part of the article a certain typology of these problems and an attempt at explanation of their background are proposed.